Traditions-Directed Approach in the Comparative Philosophy of Religion - Taheri, Javad (Poligrafi, 2022)
This paper aimed to present a novel approach to the comparative philosophy of religion which I call traditions-oriented. It is related to and yet distinct from both comparative philosophy and confessional (tradition-oriented) comparative theology. This paper begins with a reflection on the meaning and employment of ‘comparison’ in the context of philosophical analysis. What follows is an analysis of the nature of the comparative practice conducted under the umbrella concept of the comparative philosophy of religion. After sketching out the developmental trajectory of research through which a traditions-oriented, non-neutral, comparative philosophy of religion can emerge, the articulation and implementation of a global monotheistic philosophy of religion is suggested. Two case-studies from the area of Muslim-Christian comparative reflection are used to demonstrate the effectiveness of the approach developed in this paper.